Early versus later anticoagulation for stroke with atrial fibrillation - Fischer, Urs; Koga, Masatoshi; Strbian, Daniel; Branca, Mattia; Abend, Stefanie; Trelle, Sven; Paciaroni, Maurizio; Thomalla, Götz; Michel, Patrik; Nedeltchev, Krassen; Bonati, Leo H.; Gumbinger, Christoph; et al. (The New England journal of medicine, 2023)
In a large trial, the estimated incidence of stroke, systemic embolism, hemorrhage, or death was 2.8 percentage points lower to 0.5 percentage points higher with early than with later use of direct oral anticoagulants.
Online veröffentlicht: May 24, 2023
Gesehen am 08.08.2024